Borrowed Borrowings: Nahuatl Loan Words in English - Jason D. Haugen (Lexis: Journal in English Lexicology, 2009)
This paper catalogs the words of Nahuatl (aka Mexicano) origin that are attested in the Oxford English Dictionary. These words are cataloged under two classifications: semantic and chronological. Semantically, these words are grouped according to terms pertaining to zoology, botany/horticulture, culinary terms, intoxicants/psychoactives/drugs, mytho-religious terms, cultural items, cultural events, ethnological and linguistic labels, mineralogical terms, and other. Chronologically, words are attested entering the English language in each century since the 1500s, with the earliest borrowing attested in 1555 and the most recent in 1950. Loan words from Nahuatl into English are particularly interesting because they were typically not borrowed due to direct contact with speakers of Nahuatl, but secondarily through contact and trade with speakers of continental and, later, Mexican Spanish, or other European languages.